Low tunnels with shading meshes: An alternative for the management of insect pests in kale cultivation - Ponce, Franciely da Silva [UNESP]; Trento, Daiane Andréia; Toledo, Claudia Aparecida de Lima [UNESP]; Antunes, Darley Tiago; Zanuzo, Márcio Roggia; Dallacort, Rivanildo; Oliveira, Regiane Cristina [UNESP]; Seabra, Santino (Elsevier, 2021)
Kale (Brassica oleracea L. var. acephala) is one of the most cultivated leafy vegetables in Brazil. Abiotic and biotic factors can damage kale crops, reducing production and quality and making it impossible to market the product. Thus, because consumers demand sustainable production of food, the objective of this study was to evaluate the production of kale and the damage caused by pests of hybrid kale grown in different seasons and under different types of mesh. Two growing seasons, six growing environments and two kale hybrids were evaluated. The parameters evaluated were yield as measured by the total number of leaves, marketable leaves, and damaged leaves. The settlement of Myzus persicae and the damage caused by Plutella xylostella, Hellula undalis and Diabrotica speciosa were quantified. During the dry season, there was a lower yield per plant, but there was greater commercial production due to lower levels of insect infestation on plants. The use of nonwoven shade mesh reduced the damage from P. xylostella and D. speciosa on plants grown during the rainy season and reduced M. persicae during the dry season. However, cultivation under the protection of the organza fabric provided more effective protection against P. xylostella and D. speciosa, resulting in greater production of kale leaves.
Keywords: Brassica oleracea (L.) var. acephala; Plutella xylostella (L.) (Lepidoptera: Plutellidae); Protected cultivation; Screens; Shade